2015
DOI: 10.2147/ijn.s82587
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of microRNA-146a with polyethylenimine nanoparticles inhibits renal fibrosis in vivo

Abstract: Renal fibrosis is the final common pathway leading to end-stage renal disease. Although microRNA (miR) was recently shown to be involved in the development of renal fibrosis, few studies have focused on the effects on renal fibrosis of exogenous miR delivered in an in vivo therapeutic setting. The study reported here investigated the effects of miR-146a delivery using polyethylenimine nanoparticles (PEI-NPs) on renal fibrosis in vivo. PEI-NPs bearing miR-146 or control-miR (nitrogen/phosphate ratio: 6) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 45 publications
2
67
0
1
Order By: Relevance
“…Few studies have explored the relationship between miR-146a and fibrosis; Sonkoly et al 26 reported that miR-146a was significantly overexpressed in psoriatic skin lesions, which is a well-known fibrosing skin disease, compared with normal skin. Morishita et al 10 reported that miR-146a inhibited renal fibrosis by suppressing the profibrotic (Smad4-TGF-β1) and inflammation (TRAF6-NF-κB) signalling pathways. In the present study, we found that miR-146a mimics significantly decreased TGF-β-induced FN, collagen Iα and α-SMA protein production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have explored the relationship between miR-146a and fibrosis; Sonkoly et al 26 reported that miR-146a was significantly overexpressed in psoriatic skin lesions, which is a well-known fibrosing skin disease, compared with normal skin. Morishita et al 10 reported that miR-146a inhibited renal fibrosis by suppressing the profibrotic (Smad4-TGF-β1) and inflammation (TRAF6-NF-κB) signalling pathways. In the present study, we found that miR-146a mimics significantly decreased TGF-β-induced FN, collagen Iα and α-SMA protein production.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, Smad4 may be a target gene of miR-146a. Morishita et al 10 showed that the exogenous delivery of miR-146a inhibits the TGF-β/Smad and TRAF6-NF-κB signalling pathway, resulting in attenuation of renal fibrosis. The authors suggested that miR-146a may be a therapeutic option for end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PEI, a highly water-soluble cationic polymer, has been widely used for nonviral transfection of DNA and RNA in vitro and in vivo (Lu et al, 2015;Lungwitz et al, 2005;Morishita et al, 2015;Sramkova et al, 2014), and the advantage of PEI over other polycations is that it combines strong DNA compaction capacity with an intrinsic endosomolytic activity (Tang & Szoka, 1997). PEI has two structural forms, linear and branched, with various molecular masses (Fischer et al, 1999;Huh et al, 2007).…”
Section: Discussmentioning
confidence: 99%